Manufacturing Induction Heating Based on Helical Coil Method by Using Arduino Mega 2560 - Muhammad Hasan; Lenny Iryani (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
Galvanic corrosion is a type of corrosion that often occurs in aircraft structures. This type of corrosion occurs because two different types of materials contact each other through an electrolyte media. As a result of this galvanic corrosion, several components in the aircraft structure can be damaged. One example of this damage is the corrosion of the bolts on the aircraft skin. So that makes it difficult to remove from the skin. One way to loosen the bolts due to galvanic corrosion is by heating. By using induction heater to the component, the rusty bolt can be loosened. The heat generated causes the bolt to stretch and break the corrosion and so that the bolt or nut can be opened easily. In this research, by using an Arduino Mega 2560 model to remove bolts and nuts with an open loop and closed loop system was conducted. Arduino Model as a microcontroller which is needed to run a program. The specimens of the bolts are using steel bolts grade 8.8 with key sizes 13, 17, and 19. The temperature to produce induction heater is set to a temperature of 150 °C. The results show that to reach 150 oC each of the key size its produce a different duration of time. Key size 13 took 190 seconds with 35.64 watts of power, key size 17 took 279 seconds with 36.96 watts power and the 19 key took 296 seconds with 41.43 watts power.